2018
DOI: 10.1590/s1984-296120180086
|View full text |Cite
|
Sign up to set email alerts
|

Serological diagnosis and risk factors for Coxiella burnetii in goats and sheep in a semi-arid region of Northeastern Brazil

Abstract: Coxiella burnetii is a zoonotic agent transmitted mainly by small ruminants. In Brazil the disease has been classified as a notifiable disease since 2013, when human cases were reported. This study aimed to identify risk factors associated with the presence of anti- Coxiella burnetii antibodies in goats and sheep in a semiarid region of Northeastern Brazil. Sera of 412 goats and 403 sheep from municipality of Petrolina, Pernambuco, were examined by the Indirect Fluorescent Antibody Test (IFAT) against antigens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…Cleaning corrals on a daily basis reduces the chances of the spread of zoonotic diseases such as Q fever in livestock farms. A higher prevalence of C. burnetii was observed in sheep and goats in Brazil because these farms were not cleaned on a daily basis [39]. Surprisingly, animals from clean corrals actually had a lower seroprevalence compared to non-clean ones, and regardless the difference was not statistically significant in either the chi-square or multivariate analyses.…”
Section: Discussionmentioning
confidence: 88%
“…Cleaning corrals on a daily basis reduces the chances of the spread of zoonotic diseases such as Q fever in livestock farms. A higher prevalence of C. burnetii was observed in sheep and goats in Brazil because these farms were not cleaned on a daily basis [39]. Surprisingly, animals from clean corrals actually had a lower seroprevalence compared to non-clean ones, and regardless the difference was not statistically significant in either the chi-square or multivariate analyses.…”
Section: Discussionmentioning
confidence: 88%
“…In animals, C. burnetii was detected by molecular methods in 55.1% (172/312) of a herd of dairy goats with a history of reproductive disorders in the state of Alagoas (de Oliveira et al, ), and in 4 bats captured in the Atlantic forest in the states of Rio de Janeiro and Santa Catarina (Ferreira et al, ). The circulation of C. burnetii was also evidenced in the state of Pernambuco by serological methods in 2.2% (9/412) and 2.1% (9/403) in goats and sheep, respectively (Souza et al, ). In humans, two surveys were published.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, while Guimarães et al (2017) found a seropositivity rate of 2% for C. burnetii among sheep sampled in the state of Piauí, northeast of Brazil, Oliveira et al (2018) found a seroprevalence of 55.1% in a herd of goats with history of reproductive disorders in the state of Alagoas, Northeast of Brazil. Recently, Souza et al (2018) found 2.2% of the goats and 2.1% of the sheep seropositive to C. burnetii in the state of Pernambuco, also in northeastern Brazil. In southeastern Brazil, Mares-Guia et al (2014) found 66.6% seropositivity in sheep and 50% seropositivity in goats in the state of Rio de Janeiro.…”
Section: Discussionmentioning
confidence: 99%
“…The main clinical signs associated with this infection in ruminants are infertility, abortion, stillbirth, endometritis and mastitis (TISSOT-DUPONT & RAOULT, 2008). Although C. burnetii is a zoonotic agent associated with the occurrence of abortion in ruminants all over the world, there are few studies about the occurrence of this agent in ruminants in Brazil (TRAVASSOS et al, 1954apud OLIVEIRA et al, 2018MARES-GUIA et al, 2014;GUIMARÃES et al, 2017;OLIVEIRA et al, 2018;SOUZA et al, 2018). Therefore, the objective of this study was to investigate the frequency of antibodies against ruminant-selected pathogens, namely C. burnetii, BoHV-1, BVDV, N. caninum, Leptospira spp., T. gondii and T. vivax in serum samples from cattle with a history of reproductive problems from four Brazilian states.…”
Section: Introductionmentioning
confidence: 99%